PERAN PROGRAM TAHFIDZ 30 JUZ DALAM MEMBENTUK KARAKTER RELIGIUS SANTRIWATI DI PONDOK PESANTREN DARUL AMAN GOMBARA MAKASSAR - Sarmika; Yusri Muhammad Arsyad; Andi Darmawangsa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Role of the Tahfidz 30 Juz Program in Shaping the Religious Character of Santriwati at the Darul Aman Gombara Islamic Boarding School, Makassar (supervised by Dr. H. Yusri Muhammad Arsyad, MA andDr. H. Andi Darmawangsa, S.Ag., M.Ag). Education has an important role in shaping the personality and character of students so that they are able to face the challenges of the times that continue to develop. In the context of Islamic education, the formation of religious character is the main aspect that not only aims to educate intellectuals, but also to foster moral and spiritual students. One of the real efforts in shaping religious character is through the Tahfidz Al-Qur'an program. This program is not only oriented to memorization, but also to internalizing the values of the Qur'an in daily life. The research aims to: (1) Determine the role of the Tahfidz 30 Juz program in shaping the religious character of students at the Darul Aman Gombara Islamic Boarding School in Makassar; (2) Knowing the values of religious character formed through the Tahfidz 30 Juz program; (3) To know the supporting and inhibiting factors of the role of the Tahfidz 30 Juz program in shaping the religious character of the students. The research method that has been used is qualitative descriptive. Data was collected through observation, interviews and documentation. Data analysis techniques are in the form of data collection, data presentation, data reduction and conclusion drawn. The results of this study show that the Tahfidz 30 Juz program at the Darul Aman Gombara Islamic Boarding School in Makassar plays an important role in the formation of the religious character of students. Through daily, weekly, and monthly activities, students are accustomed to discipline in worship, responsibility, honesty, and patience and sincerity. The religious values that are formed include the values of worship, jihad, morals, trust, and example. The supporting factors for the success of the program come from the positive personality of the students, family support, and a religious and conducive pesantren environment. The inhibiting factors include differences in student backgrounds, inappropriate family parenting, weak motivation of some students in maintaining memorization consistency, and limited access to observation and supervision in the dormitory which causes the coaching process to not always be optimally monitored. The conclusion of this study emphasizes that the Tahfidz 30 Juz program is an effective educational means in shaping the religious character of students through habituation of Qur'anic values in daily life. An integrative and applicable approach has been proven to be able to foster discipline, responsibility, and example, although there are still several aspects that need to be improved so that the formation of religious character can run more optimally and sustainably.